Quo Vadis UUD 1945: Refleksi 67 Tahun Indonesia Berkonstitusi - Basuki, Udiyo (UIN Sunan Kalijaga Yogyakarta, 2012)
For the modern state, the constitution must be understood as a development concept. The constitution can not be viewed as a static document, but it lives and grows as the basic principle of the state organization that always followes the developments and dynamics of society. The constitution was born from constitutionalism which provides limits of state power in one side and guarantee for the rights of people through constitutional provisions in another side. During 67 years of Indonesia’s independence,the constitution give the color in the organization of state administration. Many important events woven in 3 (three) constitutions in this period, namely the Constitution of 1945, the Constitution of 1949 United Republik of Indonesia and Provisional Constitution of 1950. Departing of the view that the constitution should follow the development and dynamics of society, this paper will explore the journey of life about the constitution of the early independence to this present era. For a dynamic society, creation of awareness constitution is very important, because the constitutional talks in the future will increasingly contentious and polemical as in previous years.